2020
DOI: 10.1007/s13193-020-01241-0
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Services in Covid-19 Times: Minimally Invasive Surgery and Enhanced Recovery, the Need of the Hour

Abstract: The health services across the world have been deeply impacted by the ongoing COVID-19 pandemic which has resulted in diversion of resources to testing, isolating and treating COVID-19 patients. This meant cutting down resources and manpower away of various healthcare facilities and severely hampering the functioning of various cancer services across the world. It is however, important to understand, cancer itself is a life-threatening condition, and there is a need to continue running cancer care services, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 12 publications
(10 reference statements)
1
6
0
Order By: Relevance
“…The detailed characteristics of the included studies are shown in Table 1 . There were 16 case report [ 16 , 32 , 46 , 48 – 50 , 52 , 54 , 55 , 59 , 66 , 67 , 71 , 75 , 82 , 84 ], 9 case series, 41 cohort [ 8 17 , 23 , 25 , 26 , 29 , 31 , 34 , 43 45 , 51 , 53 , 56 58 , 60 – 65 , 68 70 , 73 , 74 , 77 , 79 , 80 , 83 , 85 ], 2 cross-sectional [ 72 , 76 ] and 1 case–control [ 81 ] studies. These studies were conducted in China ( n = 15), Italy ( n = 8), United States ( n = 6), United Kingdom ( n = 6), Spain ( n = 5), India ( n = 4), France ( n = 3), Turkey ( n = 2), Brazil ( n = 2), Japan ( n = 2), Colombia ( n = 1), Philippines ( n = 1), Poland ( n = 1), Iran ( n = 1), The Netherlands ( n = 1), Belgium ( n = 1), United Arab Emirates ( n = 1), Mexico ( n = 1), Sweden ( n = 1), Austria ( n = 1), Hungary ( n = 1), Australia ( n = 1), and Chile ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The detailed characteristics of the included studies are shown in Table 1 . There were 16 case report [ 16 , 32 , 46 , 48 – 50 , 52 , 54 , 55 , 59 , 66 , 67 , 71 , 75 , 82 , 84 ], 9 case series, 41 cohort [ 8 17 , 23 , 25 , 26 , 29 , 31 , 34 , 43 45 , 51 , 53 , 56 58 , 60 – 65 , 68 70 , 73 , 74 , 77 , 79 , 80 , 83 , 85 ], 2 cross-sectional [ 72 , 76 ] and 1 case–control [ 81 ] studies. These studies were conducted in China ( n = 15), Italy ( n = 8), United States ( n = 6), United Kingdom ( n = 6), Spain ( n = 5), India ( n = 4), France ( n = 3), Turkey ( n = 2), Brazil ( n = 2), Japan ( n = 2), Colombia ( n = 1), Philippines ( n = 1), Poland ( n = 1), Iran ( n = 1), The Netherlands ( n = 1), Belgium ( n = 1), United Arab Emirates ( n = 1), Mexico ( n = 1), Sweden ( n = 1), Austria ( n = 1), Hungary ( n = 1), Australia ( n = 1), and Chile ( n = 1).…”
Section: Resultsmentioning
confidence: 99%
“…Few studies were made within multi-countries ( n = 3) [ 9 , 12 , 51 ]. The majority of the studies were single centre [ 11 , 16 , 23 , 25 , 27 , 28 , 30 – 35 , 44 – 50 , 52 , 54 , 55 , 58 , 59 , 61 – 63 , 65 69 , 71 , 72 , 74 76 , 78 , 80 , 82 – 84 ] and only 25 studies were multi-centre [ 8 10 , 12 – 17 , 26 , 29 , 36 , 43 , 51 , 53 , 56 , 57 , 60 , 64 , 70 , 73 , 77 , 79 , 81 , 85 ]. The median NOS score for these studies was 6 (range, 5–7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations